Estudio de factibilidad para la implementación de una empresa productora y comercializadora de adornos, a base de papel reciclado en la ciudad de Loja - Brito Ponce, Jacqueline del Cisne (2016)
The objective of this research was to determine the feasibility of implementing a producer and marketer of ornaments from recycled paper, an analysis in terms of marketing, technical study and evaluation of the investment project in the City of Loja . This idea comes from the results of research and analysis to find business opportunities around the production of ornaments from recycled paper handcrafted obtaining a purely organic product. To implement this project we chose to first conduct a comprehensive study for the collection of data that will be useful to determine the feasibility of it, were surveyed people in the urban population of the city of Loja (as performed by parishes), 75.0552 inhabitants in the parish the sucre, 16,400 people in the parish the Tabernacle, 33,200 people in the parish Valley and 59,527 inhabitants in the parish of San Sebastian. In a market study it was determined that there is an effective demand for the first year of activity of the company 717,029 claimants sufficient to implement the company product. As for the offer, but does not exist in our city a producer and marketer, there is indirect offer which are 8 businesses that sell this type of craft products based on recycled paper which are the center of the city. According to the balance of supply and demand in the city have an unmet demand for ornaments 716,165 for the first year. Among the wide range of products that are classified as craft project simply artisanal products based on recycled paper, which will be new and innovative products, the price will be according to the features that are offered the product, so that customers are willing to pay $ 3.00 in mirrors and ornaments $ 2.00 ornaments in glass holder portrait. The company will cover the market of the City of Loja, mainly in bazaars, tarjeterías, exhibitions and fairs as they are the places where most frequent users or customers to make their purchases. The media that will be used to publicize the product will: Radio Society, flyers and leaflets leaves, likewise will be delivering a color brochure describing the company and the product portfolio offered. Technical study was designed to establish the necessary processes such as project engineering, plant size in which installed and used to determine what the annual production capacity of the company in this way will satisfy existing demand is set to be in the market is 73,584 units for the first year, the location of the plant, which is exactly where the company is hereby established. By legal and organizational study the type of company for the company was determined taking into account the guidelines and operating strategies, so we opted for a Limited Liability Company, and as to the organizational structure of the company has: (; oppositional functional and structural, hierarchical levels, organizational manual functions). In the study to determine the financial investment of the project is $ 29,124.45 of which $ 15,000 funding was held at the National Development Bank and the difference will solve its own capital contributed by the partners in the amount of $ 14,124.45 After completing the evaluation with different financial indexes, such as the net present value with a value of $ $ 71.703,51, an Internal Rate of Return of 94,71%, the Benefit Cost Ratio of 0.25 cents; Period Capital Recovery 1 year, 2 months and 4 days, resulting in positive indicators, which permits you to do this project without major difficulties. One of the financial indicators shows that the project is profitable is the IRR, which gives a much higher than the Minimum Acceptable Rate of Return (MARR) percentage, therefore it ensures that the project is executable.